الرّمز و التّشكيل اللّغوي في ديوان "عودة وضّاح اليمن" لعبد العزيز المقالح - نوال, حوامدي; مسعود, وقاد (جامعة الوادي - University of Eloued, 2021)
ملخص: يتغيّا هذا البحث الكشف عن التّشكيلات اللّغويّة الّتي يخلق الشّاعر من خلالها رموزا جديدة, متجاوزا بذلك الرّموز القديمة الّتي أنهكت دلاليّا, ساعيا في ذات الوقت إلى ضخّ دماء جديدة في لغته الشّعريّة . من خلال الانزياحات الّتي تخلخل البنية الدّلالية للعلامات اللّغويّة. ممّا ينتج عنه الانتقال من الدّلالات الوضعيّة إلى الدّلالات الإيحائيّة الّتي تمثّل جوهر الرّمز الشّعري. وفي سعيه ذاك لا ينفكّ عن استغلال مركزيّة الإسناد في بناء الجملة لخلق "المنافرة الدّلاليّة" الّتي ترتقي ـ في مستوياتها القصوى ـ بالعلامة اللّغويّة إلى درجة الرّمز. Abstract This research overlooks the linguistic formations through which the poet creates new symbols, by passing the old symbols that were semantically over-used, seeking at the same time to inject new blood into his poetic language through the linguistic displacement that disturbs the semantic structure of the linguistic signs. This results in a transition from the literal meanings to the suggestive connotations of signs that represent the essence of the poetic symbol. In this endeavor, the poet does not cease to exploit the centrality of attribution in the syntax of the sentence to create a "semantic dissonance" that elevates - at its maximum levels - the linguistic sign to the level of symbolism.
مقال
Keywords: الرّمز الشّعريّ؛ الدّلالة الإيحائيّة؛الانزياح السّياقي؛المنافرة الدّلاليّة؛اللّانحويّة؛الإسناد.; the poetic symbol; Suggestive sign; Contextual displacement; Semantic repulsion; ungrammaticality, attribution.